Solvothermal synthesis of Pt-Co/C cathode electrocatalyst for oxygen reduction reaction (ORR) in low temperature fuel cells - Singh A.P.; Paramanik H. (My University, 2025)
Primarily, oxygen reduction reaction (ORR) kinetics at fuel cell cathode is slower on pure platinum due to its low activity in acidic medium. Owing to the excellent electrocatalytic property of Pt-Co/C nanoparticles for the oxygen reduction reactions (ORR) in fuel cell cathodes, a cubical phase face-centered cubic (FCC) Pt-Co/C electrocatalyst has been synthesized via solvothermal method using water as solvent. Various characterization techniques, such as X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM) and Energy Dispersive X-ray spectroscopy (EDX) have been carried out for determining the crystallinity, surface morphology, particles size and elemental composition of Pt-Co/C electrocatalyst alloy, respectively. The XRD, EDX and TEM confirm the presence of well faceted FCC Pt-Co/C electrocatalyst with uniform distribution of these nano-size particles with atomic ratio of 3:1. The electrocatalytic activity of synthesized Pt-Co/C electrocatalyst for ORR was investigated by Cyclic Voltammetry (CV) test in acidic medium using HClO4. Further, as CV stop crossing is increased, the activity of Pt-Co/C electrocatalyst increases due to less activation polarization with appreciable shifting of Pt-Co/C oxygen reduction peak potential towards more positive scale confirming better electrocatalytic property of the synthesized Pt-Co/C electrocatalyst for ORR. © 2019, National Institute of Science Communication and Information Resources (NISCAIR). All rights reserved.